The Effect of the Steam Approach on Student Social Science Learning Outcomes in Elementary School - Nofia Henita; Yeni Erita; Deni Okta Nadia; Rahmi Yulia (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Community intelligence efforts can be pursued by continuing education. In Indonesia, it is very sophisticated for educators in choosing a creative and effective learning approach. One of them uses the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach. The purpose of this study is to determine the influence of this STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on the learning outcomes of grade IV elementary school students. This STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach has a positive impact on student learning outcomes because there is a significant influence on the learning of Social Sciences using this approach. Student learning outcomes using the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach are higher than learning outcomes with conventional approaches. Keywords: STEAM Approach, Learning Outcomes, Social Sciences, Elementary School.